2017 AWWA State of the Water Industry Report Results Are In!. Issue 6 (1st June 2017) - Mercer, Ken
Abstract : AWWA has tracked issues and trends in the water industry since 2004 through its State of the Water Industry (SOTWI) study. The annual SOTWI survey allows participants to serve as a voice for their colleagues and encourages reflection on the water industry's challenges and priorities. The association recently released a report detailing the study's 2017 results.